Direct aromatization of CO2 via combined CO2 hydrogenation and zeolite-based acid catalysis. Issue 45 (March 2021) - Nezam, Iman; Zhou, Wei; Gusmão, Gabriel S.; Realff, Matthew J.; Wang, Ye; Medford, Andrew J.; Jones, Christopher W.
Highlights: Two main categories of tandem catalysts for CO2 aromatization are reviewed. Key parameters that determine the catalytic performance are assessed. Thermodynamic analysis, mechanistic studies, and DFT computations are analyzed. The challenges and prospects for these tandem reactions are addressed. Abstract: Aromatics, including benzene, toluene, and xylenes (BTX), are essential chemical building blocks and are widely used as solvents, fuel additives, and polymers. With the recent development in CO2 capture technologies and the progress made in producing H2 using renewable energy, direct hydrogenation of CO2 to aromatics via heterogeneous catalysis has emerged as a promising pathway to accomplish the production of aromatics with simultaneous utilization of waste CO2 . In this review, we focus on recent advances in the nascent field of direct CO2 aromatization, whereby tandem catalysts composed of CO2 hydrogenation and aromatization functionalities are designed and deployed. We review two categories of tandem catalysts: catalysts integrating Fe-based/H-ZSM-5 components following RWGS (reverse water-gas shift of CO2 to CO)-FT (Fischer-Tropsch synthesis of lower olefins)-aromatization pathways, and catalysts combining metal oxide/H-ZSM-5 domains following CO2 to methanol-aromatization pathways. The key parameters that determine the catalytic performance, such as the composition and structure of the Fe-based or metal oxide-based CO2 conversion catalysts, the properties of H-ZSM-5, and the synergy between the two components, are analyzed to provide insights for the design of efficient tandem catalysts for CO2 aromatization. In parallel, thermodynamic analyses, mechanistic studies, and density functional theory (DFT) computations for the relevant reaction routes and pathways are discussed to offer improved understanding of CO2 activation, reaction intermediates, and product formation. Finally, the challenges and prospects for these tandem reactions are addressed to provide suggested paths forward for future research.